BAHASA MOTIVASI YANG DIGUNAKAN INDUSTRI KREATIF DI MAKASSAR: Motivational Language Used by the Creative Industry in Makassar - Sarifah; Usman; Hajrah (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
The motivational language used by the creative industry in Makassar. This study aims to describe the types of motivational language in the creative industry and describe the function of motivational language in the creative industry. The research method used in this study is qualitative research that is descriptive. In this study, researchers try to describe the object or subject of belittling systematically and objectively so that facts can be described carefully precisely. The results showed that the type of motivational language is divided into two, intrinsic and extrinsic motivation. The language of intrinsic motivation contains messages and principles that guide individuals to grow, develop and achieve potential in the creative industries. Extrinsic motivation contains messages that reflect and encourage the specific cultural and social values of the creative industry.